Stroke Treatment Cost Analysis for Consideration on Health Cost Determination Using INA- CBGs at Jogja Hospital - Ingenida Hadning; Zullies Ikawati; Tri Murti Andayani (International Journal of Public Health Science (IJPHS), 2015)
Indonesian Case Based Groups (INA-CBGs) implementation on hospital financing for stroke patient using Jaminan Kesehatan Masyarakat (Jamkesmas) at 3rd class hospitalization requires therapy plan management and cost analysis because stroke is a leading cause of death worldwide and need high treatment cost. It is purposed to skimp the hospital expenditure and avoid deficit suffering. The study objectives was to determine the suitability cost between real stroke treatment cost and health financing based on INA-CBGs, and to determine the highest cost component on stroke treatment at Jogja hospital. This cross sectional observational study used retrospective sampling method. The subjects were taken from all stroke patient population using Jamkesmas insurance at Jogja Hospital, were hospitalized between January 2011-April 2012 and met the inclusion criteria. The subject was then classified based on INA-CBGs. Patient’s length of stay and costs (direct medical and direct non-medical costs) were defined as study variable. Data was analysed using descriptive analysis and Mann Whitney test. Throuh this study we conclude the average rate of real stroke treatment cost at Jogja Hospital was higher insignificantly than INA-CBGs based cost and the highest treatment cost was on the medicine and medical equipment.